Investigation of the effectiveness of the chancel availability and geometry of four traditional churches in Malaysia: Simulation experiment - Abd Jalil, Nurul Amira; Che Din, Nazli; Cheryl Yew, Shyh-Qi; Pradeepa, Chandramouli; Putra, Azma; Azeem, Waqar (MDPI, 2023)
Two significant spaces define the soundscape of worship in a church: chancel and nave. The chancel is a space with the primary function of a sound source, where the preachers and choir are often seated during church services. Church design and layout have changed throughout history based on the functional needs of its target congregation. Some modern churches have omitted the chancel to fit contemporary design aesthetics. The main aim of this study is to investigate the relationship between the chancel and the acoustics performance of a church. Four churches with varying geometries of circular, polygonal, and rectangular chancels were selected for this study. Two simulations of varying chancel characteristics of chancel availability and chancel geometry were conducted. The recorded speech intelligibility index (STI) and reverberation time (RT) results indicate that chancel availability and geometry significantly affect churches’ acoustic performance. The simulation of the chancel availability mainly affected speech intelligibility, where the models with chancels recorded a higher STI than the models without chancels. In terms of chancel geometry, the results of the STI of the circular chancels were more encouraging than the polygonal and rectangular chancels